2015
DOI: 10.1111/hae.12653
|View full text |Cite
|
Sign up to set email alerts
|

Platelet function analyser (PFA‐100) results and von Willebrand factor deficiency: a 16‐year ‘real‐world’ experience

Abstract: The platelet function analyser (PFA-100) is a biological tool designed to explore primary haemostasis. This system has thus been widely demonstrated as reliable in detecting von Willebrand factor (VWF) deficiency. However, most studies were based on patients benefitting from regular medical care and accurate diagnosis, and it would seem probable that the results were somewhat optimistic, and do not reflect its performances in 'real-world' situations. We have chosen to study the reliability of PFA-100 for scree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
42
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 23 publications
2
42
0
Order By: Relevance
“…These VWF‐dependent platelet function analyses are performed without additional technical manipulation, and PFA enables the measurement of the impact of high shear stress blood. In our study, prolonged CT with PFA was detected in all VWD types, supporting the inclusion of platelet contribution and the use of this assay, among conflicting previous reports . These tests can add value as screening tools and provide support for challenging diagnostics.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…These VWF‐dependent platelet function analyses are performed without additional technical manipulation, and PFA enables the measurement of the impact of high shear stress blood. In our study, prolonged CT with PFA was detected in all VWD types, supporting the inclusion of platelet contribution and the use of this assay, among conflicting previous reports . These tests can add value as screening tools and provide support for challenging diagnostics.…”
Section: Discussionsupporting
confidence: 86%
“…No blood flow and shear force‐based clinical assays are in routine use. The role of the platelet function analyzer PFA‐100 ® (PFA), a primary hemostasis screening tool under high shear stress, is under debate . Multiplate ® (Multiplate) is a next‐generation automated whole blood aggregometry device that does not require additional technical manipulation .…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the first publication on the Thrombostat-4000 only appeared two years earlier, in 1993 [17]. It is therefore fitting that the current issue of Haemophilia includes a contribution [18] on the PFA-100 from a French group who first wrote of their initial experience with this instrument in 1998 [7]. A recent Medline search of 'Thrombostat-4000' yielded only 23 papers; these were published in the period 1993-2001 (a total of 9 years).…”
mentioning
confidence: 99%
“…For example, using local external quality assessment (EQA) data, the inter-laboratory coefficient of variation (CV) for VWF:RCo averaged~50% for samples tested in the last decade [2]. Although these CVs reflect inter-laboratory variation, and the data from Ardillon et al [18] report on a single laboratory, one could propose that intra-laboratory variation, plus intra-individual variation, may also be either comparable, or perhaps even favourable for the PFA-100, depending on the method in use for the VWF:RCo. For the PFA-100, there is only the one instrument, and generally only two cartridges used for VWD testing.…”
mentioning
confidence: 99%
“…In people, the PFA is used as a screening test for vWD (Ardillon et al . ). One study reported increased CTs in 2 dogs with vWD that responded to DDAVP treatment (Burgess et al .…”
Section: Specific Tests Of Platelet Functionmentioning
confidence: 97%